Re-examining the Relationship Between Need for Cognition and Creativity: Predicting Creative Problem Solving Across Multiple Domains. Issue 1 (2nd January 2017) - Watts, Logan L.; Steele, Logan M.; Song, Hairong
Abstract : Prior studies have demonstrated inconsistent findings with regard to the relationship between need for cognition and creativity. In our study, measurement issues were explored as a potential source of these inconsistencies. Structural equation modeling techniques were used to examine the factor structure underlying the 18-item need for cognition scale in three independent samples drawn from three prior studies. In addition, the relationships between need for cognition and the quality, originality, and elegance of creative problem solutions across multiple domains of performance were analyzed. Across all 3 samples, the bifactor model fit the data better than the 2-factor and 1-factor need for cognition models. After controlling for method-specific variance, the trait factor of the bifactor model showed consistently positive relationships with all 3 facets of creative performance and showed stronger relationships with these facets than the composite score results reported in prior studies. Implications for research and practice are discussed.